Теория марксизма и современное человечество - Шевченко, А. С. (ХНУРЕ, 2020)
There are at least two camps of representatives of science and the public regarding the significance of Marxism today. Some say that K. Marx’s ideas are outdated, others say that they are still in demand today. Have the ideas of a wellknown economist lost their relevance today?
Keywords: философия